Closed-form solutions for drug transport through controlled-release devices in two and three dimensions - Simon, Laurent, 1968-; Ospina, Juan, 1965- (John Wiley & Sons Inc., 2016)
"Covers the modeling of drug-delivery systems and provides mathematical tools to evaluate and build controlled-release devices"--Provided by publisher.